ANALYSIS OF SHIFT WORKING SYSTEMS ON THE WORK FATIGUE LEVEL AT GAS STATION OPERATOR USING BOURDON WIERSMA METHOD - Dita Meireza; Suroto Suroto; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Shift work is a system applied by companies to maximize and maintain productivies for 24 hours which is divided into morning, afternoon and night works. Fatigue is a condition of reduced efficiency, performance and reduced strength or endurance of the body to continue activities. The implementation of shift work that causes work fatigue have to be controlled considering fatigue can cause workplace accidents. The purpose of this research is to analyze the correlation between shift work with the fatigue of work on the gas stations operator using Bourdon Wiersma methods. This research type is a cross-sectional analytical descriptive research. The population and sample in this study are 33, operators “gas station 44 502 23 and gas stations 44 502 02 Semarang. The instrument that use in this research were Bourdon Wiersma test form to evaluate speed, accurary and constancy. The results showed that there was a correlation between shift work and fatigue (sig 0.032). Most operators feel heavy fatigue when working on the night shift (63.6%) compared to day shifts (36.4%) and morning shifts (18.2%) To reduce the fatigue of work on the operator, management should replace the regulation of “shift work system” to “quick rotation pattern” that is 2-2-3 and 3-3-2 systems so the operators can adapt to their work schedule.